Six Sigma to Enhance Time Efficiency and Quality in Nepal's Construction Sector - Mostafa, Singh Samir (Journal of Progress in Civil Engineering, 2025)
The world has taken the word “construction” as nation developing phenomena. The country’s economic and social development depends upon its rate of productive construction. The productivity is acquired if time and quality of construction has taken into consideration. There were various methods of increasing the construction productivity such as Project Management Technique- Critical Path Method, Program Evaluation and Review Technique etc. These techniques some-how increased the construction efficiency but it didn’t obtain the required expectation. Thus, Six-Sigma- as a philosophy, which was considered in this paper. The five phases of Six-Sigma will provide the systematic way to increase the efficiency. Define(D), Measure(M), Analyze(A), Improve(I) and Control(C) are the five phases of Six Sigma. The paper is based on two work portions, one with questionnaire and other is practical use of Six Sigma in construction industry. The questionnaire was sent to 100 individuals out of which only 60 questionnaires were retrieved. The obtained questionnaire was evaluated with the RII (Relative Importance Index) method. The case study in which six- sigma was used is of internal tiling work for a residential building. The flat was of 2BHK and 2 numbers of flat were observed. The initial tiling work was evaluated without any direction and the sigma level was 2.08. After applying the Six Sigma Concept, the obtained level was 3.7. Hence, this research paper demonstrate that Six-Sigma is able to optimize and improve time and quality of construction projects.